Estudio del Blockchain como alternativa dentro de la gestión del Ingeniero Industrial. - Guerrón Delgado, Dayana Ivanova (2020)
The globalization of markets has prompted industries to implement improvements in their processes in order to make them efficient, in order to offer their customers products and services in the quantity, quality, place and time required, all while minimizing costs. associated with these activities. Among the different transformations that have occurred in the industrial sector is the logistics where the lack of transparency, poor documentation management, quality control and digitization is no longer a problem because Blockchain manages to transform and improve the management of industries, it also speeds up large-scale data exchange processes, eliminating the long and complex procedures executed on paper, for a sustainable system with the environment. The present investigative project for its development of the theoretical foundation of the variables that intervene in the subject of study, techniques and instruments were developed as an important part for the development of the investigation, applying the documentary approach that helped to collect and analyze the data. The sources of information that were used in the investigation were primary and secondary, as well as the descriptive investigation, the same ones that allowed the analysis of the operation of the technology highlighting its benefits that it contributes to the industry to identify the fields of application of the technology. Industrial Engineer in which it is feasible to incorporate Blockchain technology, finally, for its subsequent interpretation, it was done through a case study in the supply chain. Consequently, the present study shows, after having analyzed three case studies in the industry, the field that has the greatest feasibility of applying Blockchain technology is logistics, since it allows processes to be accelerated and automated, facilitating the management of Industrial Engineering. intermediaries, reduction of time and costs in the different operations presented in the supply chain and at the same time simplification in payment methods that are executed in minutes thanks to the intervention of intelligent contracts, achieving quality and efficiency.